Epidemiology of paediatric pain-related visits to emergency departments in the USA: a cross-sectional study - Molly Moore Jeffery; Fernanda Bellolio; Jana L Anderson; Lucas Oliveira J. e Silva; Shealeigh A. Funni (BMJ Open)
Objective To describe the epidemiology of paediatric pain-related visits to emergency departments (EDs) across the USA.Design Cross-sectional study.Setting A representative sample of US ED visits using data from the National Hospital Ambulatory Medical Care Survey (NHAMCS).Participants Paediatric (age ≤18 years) ED visits in the 2017 NHAMCS data set.Data analysis Each visit was coded as pain-related or non-pain-related using the ‘reason for visit’ variable. Weighted proportions were calculated with 95% CIs. Logistic regression was used to compare odds of pain-related visits.Outcome measures Prevalence of pain-related visits among paediatric ED visits.Results There were an estimated 35 million paediatric ED visits in the USA in 2017, 55.6% (CI 53.3% to 57.8%) were pain related, which equates to 19.7 million annual visits. The prevalence of pain-related visits reached more than 50% of visits at age 6–7 and plateaued at relatively high proportions. Children of races other than white or black had lower odds of having a pain-related visit (OR 0.48, CI 0.29 to 0.81) than white children, as did children who were black, though the difference was not statistically significant (OR 0.88, CI 0.73 to 1.06). Relative to children covered by private insurance, children with Medicaid or CHIP (Children’s Health Insurance Program) coverage had lower odds of a pain-related visit (OR 0.75, CI 0.60 to 0.93). Injuries represented 46.5% (CI 42.0% to 51.0%) of pain-related visits. Pain scores were reported in less than 50% of pain-related visits.Conclusion Pain is the reason for visit in 55.6% of paediatric ED visits across the USA. The prevalence of pain-related visits peak before adolescence and it continues relatively high until the age 18. Injury, racial disparities in pain and poor pain score reporting should remain major topics of study in the paediatric population.